Shape Reconstruction using Overset Grid Generation Method with an Iterative Inversion Technique - Azarina, Binti Azman (Universiti Malaysia Sarawak (UNIMAS), 2020)
Detection of buried objects has been of significant interest for many researchers in a variety of fields. The unknown dielectric profile of buried object has been determined using an electromagnetic (EM) inverse scattering technique. This technique is generally developed in both the time-domain and the frequency-domain. The time-domain scattering data contains more information and has the potential to reconstruct the dielectric properties more accurately compared to a single frequency scattering data. The time-domain inverse-scattering technique referred to as Forward-Backward Time-Stepping (FBTS) technique is proposed to formulate the inverse scattering technique in time-domain by utilizing Finite-Difference Time-Domain (FDTD) method. The FDTD method is a widely used scheme in approximating electromagnetic waves. The FBTS technique utilizing the combination of Overset Grid Generation and Finite-Difference Time-Domain (OGG-FDTD) method is one of the inverse scattering techniques in time domain in which is applied to object detection and reconstruction. The FBTS algorithm is implemented in C++ language executed in a single computing by developing the time-domain form of the OGG-FDTD method to reconstruct dielectric profile of unknown object. In OGG-FDTD method a system of relatively simple meshes are used to reduce the geometrically complex problem to a simple set of grids. The validity of the FBTS algorithm utilizing OGG-FDTD method is carried out for direct problem and inverse problem. For direct problem, the results show good agreements are obtained with the reference signals. For inverse problem, the proposed technique is able to detect the embedded object at the centre of ROI as small as 10 mm in radius and also capable to reconstruct small square object with size of 10 mm × 10 mm. The reconstruction results demonstrated that the FBTS technique utilizing OGG-FDTD method has the ability to detect and reconstructed embedded object.